Coaches' self-awareness of timing, nature and intent of verbal instructions to athletes - Millar, S.; Oldham, A. R. H.; Donovan, M. (International Journal of Sports Science and Coaching, 2011)
Coach development literature identifies the need for coaches to be self-aware regarding their impact on athletes. Here, four English rowing coaches were observed and their ability to accurately identify the type, nature and timing of verbal instructions used while coaching was examined. For one training session, every verbal instruction delivered by the coaches was coded, using an adapted version of the Feedback Analysis Profile (FAP). At the end of the session, coaches completed an indepth questionnaire about their perceived verbal behaviour. Results showed that the coaches were inaccurate when recalling what was said to athletes. Coaches were observed giving predominantly concurrent (while athletes were rowing) and prescriptive (what to do) instructions. Results also showed minimal use of evaluative (was it any good?) or affective (how did it feel?) feedback. Coaches' perceptions did not match recorded data, highlighting the need to develop methods which increase coach self-awareness.